Edukasi Prenatal Yoga Upaya Mengatasi Nyeri Punggung Bagian Bawah Pada Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Astambul - -, Isrowiyatun Daiyah; Zakiah; Fitria Jannatul Laili; Melinda Putri Anggreani; Amalia Zahra; Nurul Annisa Maizarah (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
Background: Efforts to overcome or reduce lower back discomfort include doing yoga before labor, which includes breathing and warm-up, stretching exercises, core exercises, and gentle and slow relaxation. Based on data from the UPTD Puskesmas Astambul in 2023, there were 22 classes of pregnant women and the average pregnant woman was in the third trimester, where the pregnant class activities were often lecture and question and answer methods, and there was no information about prenatal yoga in pregnant class activities, it did not rule out the possibility of complaints of discomfort in the lower back experienced by mothers in pregnant classes. Information obtained from the midwife coordinator of the Astambul Health Center has never been a service activity or research related to prenatal yoga, as well as the material in pregnant classes has never provided material about prenatal yoga. Objective: This study aims to increase the knowledge and skills of pregnant women about prenatal yoga to reduce lower back pain in pregnant women's classes and community empowerment in sustainable application of prenatal yoga in pregnant women's classes in the Astambul area, Astambul District, Banjar Regency. Methods: The health and community empowerment community service program utilizes extension and communication, information, and education (IEC) approaches to implement these community service activities. This process includes preparation, implementation, and supervision and evaluation of activities. This activity involved 10 pregnant women. Results: Evaluation of activities shows a decrease in the lower back pain scale of pregnant women. A total of 7 people (70%) who experienced moderate pain and 3 people (30%) in the pre-intervention and there was a decrease in the pain scale of all respondents to mild pain, namely 10 people (100%) in the post intervention. Conclusion: this decrease in pain scale is expected to contribute to efforts to overcome lower back pain in the class of pregnant women.